Single session intermittent heat exposure with more frequent and shorter cooling breaks facilitates greater training intensity and elicits physiological responses comparable to continuous heat exposure - Ramos, J. A. P.; Ducker, K. J.; Riddell, H.; Landers, G.; Girard, O.; Brade, C. J. (International Journal of Sports Physiology and Performance, 2024)
Purpose To investigate the influence of shorter, more frequent rest breaks with per-cooling as an alternative heat-acclimation session on physiological, perceptual, and self-paced maximal cycling performance, compared with continuous heat exposure.